Treatment of radiation dermatitis in the light of evidence-based medicine - Topczewska-Bruns, Joanna; Filipowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2010)
A large part of oncological patients will be treated using radiation therapy. The effect of the action of ionizing radiation on the skin is radiation dermatitis, which may have a different level of intensity. Skin reaction is a source of a number of ailments such as burning, itching or pain on the irradiated area. A severe degree of radiation dermatitis can not only significantly impair quality of life of the patient, but also require the interruption of irradiation which can influence results. Prevention and treatment of radiation skin reaction is a daily practice for radiotherapist, but unfortunately, there is little evidence on which to base therapeutic decisions. This article presents a review of clinical trials for the prevention and treatment of radiation dermatitis.